WACANA TANPA OSPEK, UNAS SAMBUT MAHASISWA BARU LEWAT CHARACTER BUILDING (Analisis Wacana Kritis pada Berita) - Adi Prakosa (Universitas Nasional, 2018)
Ospek and Character Building are two concepts offered by news writers to news readers. The Ospect has a spooky connotation. In fact, some students become victims of ospek activities, some even died. Character building has a convenient connotation. This research seeks to review the news entitled